L'alignement de l'enseignement supérieur ouest-africain - Eliethe P. Éyébiyi (Les éditions de la Maison des sciences de l'Homme, 2011)
The privatization of higher education has become in Africa in the context marked by the democratization and the disqualification of the State. If it practice is calamitous (Eyebiyi, 2010) and generates unforeseen processes, West African States, firmly fastened to the French model, should nowadays integrates the LMD reform. Between international requirements and local adaptations, the lining up of West Africa on unified European model of Bologna Process is include more than the passage from quantitative aspects, in the frame of higher education merchandising. The unbridled quest of professionalization causes deeply changes in the curricula and drives the reconstruction of the local and national knowledge fields.